Impact of isoflavones and probiotics on human gut health and bone health: A review - J, Thivya,; S, Deepa,; Olalekan, Adeyeye, Samuel Ayofemi (Edelweiss Applied Science and Technology, 2026)
This review aims to evaluate how isoflavones and probiotics influence gut microbiota, immunity, and bone health, and to examine the bioactive and nutritional properties of soybean and sorghum for developing synergistic, functional, value-added probiotic beverages. This review employed a systematic literature search across scientific databases to gather studies on gut microbiota, isoflavones, probiotics, and functional beverages. Relevant findings were analyzed, compared, and synthesized to evaluate bioactive interactions, health impacts, and the functional potential of soybean–sorghum probiotic formulations. The findings highlight the crucial role of gut microbiota in immunity and disease prevention, showing that disruptions contribute to major disorders such as obesity, diabetes, and cardiovascular disease. Isoflavones significantly influence gut microbial balance by promoting beneficial bacteria and inhibiting pathogens, while also supporting bone health through metabolites like equol. Probiotics similarly enhance hormonal, immune, and digestive functions. Combined, probiotics and isoflavones offer synergistic benefits, improving calcium absorption, gut modulation, and metabolic health. Soybean and sorghum bioactives demonstrate strong potential for functional probiotic beverage development. Isoflavones and probiotics synergistically enhance gut microbiota balance, immunity, and bone health, supporting the development of nutritious functional beverages. Their combined metabolic and bioactive effects show strong potential, though further research is required.